Nos trilhos da morte : tragédia ferroviária, debate judicial e racismo em Sergipe nos anos 40 - Bezerra, Luiz Paulo Santos (2017)
In 1946, between the municipalities of Riachuelo and Laranjeiras, in Sergipe, more precisely at kilometer 458 of BR 101, a serious train accident occurs, which enters to history as the largest rail disaster in Brazil. In it, known by the victims as "the suburban train", several people of different occupations (merchant, marketer, mason, fisherman among others) and from several regions of the interior of Sergipe traveled for commercial purposes. Dozens of dead and several injured were found at the site of the disaster, and survivors reported the incident in a criminal case of approximately 400 pages. The study we intend to present in this work becomes important, as there are still no historical reports of researchers who analyzed the biggest railway disaster in Brazil. This makes our work an unpublished research, having as a parameter the lack of complete materials at the national and regional / local level, leaving us incomplete references. Our main objective, therefore, is to reconstitute a judicial system that involved the appalling accident. We will try to analyze and pursue all the characters who were involved directly and indirectly in the episode. We will try to give visibility to forgotten subjects, the racial theories that surrounded the period, the memories and everyday scenes of a post-war Sergipe. We used for the writing, judicial sources, as the crime process to which all the plot is passed and from where we found the characters that will be mentioned while the chapters. The newspapers will become a very precious source, because we will know if the news of the disaster has touched Brazil and the world. As a strong mean of communication, newspaper reports will give us, to a certain extent, a glimpse of how the stories were spread and how journalistic circles saw the tragedy. The memories and chronicles, not least important, will contribute as a revealing material of the daily and scenario that we are analyzing. Finally, I add the Vox populi, the Cordel of Rodolfo Coelho Cavalcante from Alagoas, who portrayed the tragedy in verse and prose. The method we used for the cataloging of data was the same revealed by Carlo Ginzburg in several of his works, the indicial paradigm, in view of our search for clues that reveal the concrete guilt of the tragedy and the complex ideological reality of the 1930s and 1940, in which solidified racial ideas were circulating in the world and in Brazil.